Recent progress on flutter‐based wind energy harvesting - Li, Zhiyuan; Zhou, Shengxi; Yang, Zhichun (International journal of mechanical system dynamics, 2022)
Wind energy harvesting technology can convert wind energy into electric energy to supply power for microelectronic devices. It has great potential in many specific applications and environments, such as remote areas, sea surfaces, mountains, and so on. Over the past few years, flutter‐based wind energy harvesting, which generates electric energy based on the limit cycle oscillation created by structural aeroelastic instability, has received increasing attention, and as a consequence, different energy harvesting structures, theories, and methods have been proposed. In this paper, three types of flutter‐based energy harvesters (FEHs) including airfoil‐based, flat plate‐based, and flexible body‐based FEHs are reviewed, and related concepts and theoretical models are introduced. The recent progress in FEH performance enhancement methods is classified into structural improvement and optimization, the introduction of nonlinearity, and hybrid structures and mechanisms. Finally, the main FEH challenges are summarized, and future research directions are discussed.